First report on the gall wasp Ophelimus near migdanorum (Hymenoptera, Eulophidae) and its parasitoid Closterocerus chamaeleon (Hymenoptera, Eulophidae) in Eucalyptus globulus in Bogotá, Colombia - Pinzón-Florián, Olga (Zookeys, 2020)
Abstract. Ophelimus near migdanorum, a foliage gall wasp-inducer of Eucalyptus, is recorded for the first time in Colombia, infesting both mature ornamental trees of Eucalyptus globulus (Labill.) and monoculture plantations in the periurban forest in the city of Bogotá. The parasitoid Closterocerus chamaeleon was also emerged from the galled foliage. The spread of this pest and its parasitoid in other Eucalyptus species planted in Colombia has not been evaluated.